Mapas topográficos: metadados e as regras de catalogação para o acesso eficiente à informação geográfica - Alencar, Cely Martins Santos de [UNESP] (2014)
The growing availability of geospatial data, the diversity of geographic information environments and the continuous technological advances have enabled the development of methods and applications for descriptive treatment. That is the case of metadata standards allowing new practical approaches, especially in a digital environment. Government agencies, as major producers of cartographic material, are demanded to publish it in an open, transparent and machine-processable form. The access and use of these resources depend on proper standardization and technical specifications. Topographic maps are resources resulting from cartographic techniques and constitute reference items, with attributes and specificities that represent the territory, and are essential for public policies. The occurrence of various metadata standards indicates that the cartographic materials require studies about formats' compatibility and adequacy of description schemes. From the definition of metadata record, in order to meet specific requirements, emerges the question of: how to efficiently describe the cartographic materials and, more specifically, digital topographic maps? The thesis is that the presentation of digital topographic maps in an accessible format, with appropriate and unambiguous descriptions, facilitates their identification and location and, ultimately, its use. The proposition of this thesis is to analyze the theoretical Cataloguing framework that guides the standardized construction, in order to provide the fundamental principles and values to maps registry. The main goal is to contribute to the proper description and quality of Topographic Maps to meet the specific requisites and provide interoperability. In order to achieve this goal, analyses were made about the description scheme of the MGB to AACR2r profiles and the correspondence between the MGB profile and the MARC 21 format. As a result, a systematization of the relationships between...